The distribution of Moose (Alces alces) during winter in southern Sweden : a response to food sources? - Wallén, Mikael (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2010)
The traditional Swedish way of dealing with browsing damages made by moose, is to reduce the moose population. However, a growing way of dealing with damages made by several ungulate species, including wild boars in particular is to redistribute them with supplementary food sources. Attracting them to settle in habitats less vulnerable to damages made during foraging. This study we tracked collared moose in southern Sweden from January throughout April in the year of 2009. From the tracking data their “favourite” positions was selected and visited in order to study the features that attracts moose during winter. Later the results from this survey was analysed in order to determine how these feature affects the distribution of moose. The main hypothesis tested in this study are, that moose could be redistributed in their home range by providing supplementary food sources. The results of the study indicates that moose are attracted to supplementary feeding stations set up by man, which give forest managers an opportunity to use them as a tool to redistribute moose into areas with less vulnerable forest stands, with a maintained overall density of moose. Like many other studies this one also results in Pine and Birch are the bulk food source to moose, but this study also suggests that shrubs like bilberry, foxberry and heather are preferred food sources to moose in southern Sweden.